Chemical composition and pharmacological activity of ethanol extract of Satureja sericea (goyal) - Bonilla Rivera, Pablo E (2011)
We studied the aerial parts of Satureja sericea (goyal) of the Mallas community, Huari province, Ancash Region, used for diseases of the digestive tract due to its carminative and anti-inflammatory properties. The sample was dried under shade, powdered and the extract was obtained by maceration in ethanol. In solubility and phytochemical screening was observed large amount of phenolic compounds. It was confirmed the presence of four flavonoids by color reactions and precipitation; this flavonoids were isolated by thin layer chromatography to preparative-scale and their structures were elucidated by UV visible spectroscopy in ethanol and displacement reagents. The cytoprotective effect on the gastric mucosa was evaluated by oral administration of alcoholic extract in rats. It was also evaluated the gastric antisecretory effect of ethanol extract in rats subjected to pyloric ligation. Safety was evaluated in animals by oral acute toxicity, repeated dose for 28 days abd determining the DL50 . The lethal dose 50 of the ethanol extract was determined in mice; the hematological, biochemical and histopathological parameters were evaluated) using the model of repeated dose toxicity when given orally oral ethanol extract to normal rats according to OECD.